Essays in the economics of banking - Michis, Antonios (Τμήμα Εμπορίου, Χρηματοοικονομικών και Ναυτιλίας, Σχολή Διοίκησης και Οικονομίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2014)
This thesis examines different aspects of the determinants of interest rates in the banking industry by using techniques associated with the fields of industrial organization and financial economics. It proposes that equilibrium interest rates, as observed in the banking industry, are the complex outcome of many different market forces in the economic system that cannot be adequately explained by only one branch of financial economics. Three topics are examined in detail: (1) measurement of market power and its impact on lending interest rates, (2) the use of nonlinear pricing tactics by banks in order to improve profitability and the influence of market structure and (3) time-scale estimation of the liquidity effect in an economy, following monetary policy changes. In Chapter 1 a conjectural variations model is developed to measure market power in the banking industry. Unlike previous studies, which use complete cost function specifications in the modelling framework, this study defines marginal cost based on an opportunity cost, which is represented by the interest rate on minimum reserves offered by the monetary authorities in a country. Deposits with the monetary authorities are considered to be an alternative use of available funds that are usually allocated to loans. The estimates of market power in the banking industry in Cyprus, using the proposed model, reject the monopoly hypothesis. In Chapter 2 an econometric test is proposed to verify the existence of nonlinear pricing for loans in the European credit market. The test is based on Baumol’s model of cash demand and incorporates an industry concentration measure in order to examine the impact of market structure on the provision of quantity discounts (nonlinear pricing). The econometric results, using a panel dataset consisting of seven European countries and a fixed effects model specification, suggest that nonlinear pricing is associated with increasing monopoly power in the European banking industry. Chapter 3 examines the existence of a liquidity effect in the UK economy over different time-scales. This analysis draws from the liquidity preference framework, an approach to interest rate determination, and uses wavelet multiscale analysis in the context of a standardised regression model. The results suggest that, in short-term cycles, interest rates are influenced primarily by changes in the money supply (i.e., the liquidity effect). In medium- and long-term cycles, the liquidity effect becomes less important and interest rates are found to be more sensitive to income and price effects. The average duration of the liquidity effect is estimated to be less than 8 months.
Keywords: Interest rates; Banking industry; Idustrial organization; Financial economics